Ferroelectric Self‐Poling, Switching, and Monoclinic Domain Configuration in BiFeO3 Thin Films. (23rd May 2016) - Beekman, C.; Siemons, W.; Chi, M.; Balke, N.; Howe, J. Y.; Ward, T. Z.; Maksymovych, P.; Budai, J. D.; Tischler, J. Z.; Xu, R.; Liu, W.; Christen, H. M.
Abstract : Self‐poling of ferroelectric films, i.e., a preferred, uniform direction of the ferroelectric polarization in as‐grown samples is often observed yet poorly understood despite its importance for device applications. The multiferroic perovskite BiFeO3, which crystallizes in two distinct structural polymorphs depending on applied epitaxial strain, is well known to exhibit self‐poling. This study investigates the effect of self‐poling on the monoclinic domain configuration and the switching properties of the two polymorphs of BiFeO3 ( R ′ and T ′) in thin films grown on LaAlO3 substrates with slightly different La0.3 Sr0.7 MnO3 buffer layers. This study shows that the polarization state formed during the growth acts as "imprint" on the polarization and that switching the polarization away from this self‐poled direction can only be done at the expense of the sample's monoclinic domain configuration. The observed reduction of the monoclinic domain size is largely reversible; hence, the domain size is restored when the polarization is switched back to its original orientation. This is a direct consequence of the growth taking place in the polar phase (below T c ). Switching the polarization away from the preferred configuration, in which defects and domain patterns synergistically minimize the system's energy, leads to a domain state with smaller (and more highly strained and distorted) monoclinic domains. Abstract : Defects formed and charges trapped during growth at the ferroelectric/electrode interface and within the film determine the lowest energy domain configuration and strain state of BiFeO3 films. Polarization reversal thus leads to the formation of an energetically less favorable domain and strain state with smaller monoclinic domains and weaker X‐ray diffraction intensity.